Depressed Kallikrein Generation in Women With Preeclampsia: A Matched Cross-Sectional Study - Godtfredsen, Anne Cathrine; Gram, Jørgen Brodersen; Pham, Stephanie Thuy Duong; Dolleris, Britta Blume; Jørgensen, Jan Stener; Sidelmann, Johannes Jakobsen; Palarasah, Yaseelan (Frontiers in Medicine, 2022)
Objective The pathophysiology of preeclampsia is not fully understood. Disturbances in the contact system are associated with PE. Few studies have investigated the association between preeclampsia and alterations in the contact system in plasma. This study aims to elucidate whether this basic biological system is affected by preeclampsia using new methods focusing on the dynamic interactions and total capacity of the contact system in blood. Design Cross-sectional study matching women with preeclampsia and controls without preeclampsia regarding age, pregestational body mass index, and gestational age at onset of the disease. Setting Two Danish University hospitals. Sample A cohort of 117 women with preeclampsia and 117 controls. Methods The turnover and capacity of the contact system were determined with new methods. Paired t-test, Wilcoxon signed-pairs signed rank test, Mann-Whitney or Chi2-test were applied, as appropriate. Main outcome measurements Kallikrein generation (peak kallikrein concentration and endogenous kallikrein potential), coagulation factor XII, prekallikrein, H-Kininogen, cleaved H-kininogen, and complement C1 esterase inhibitor. Results The endogenous kallikrein potential, peak kallikrein concentration, prekallikrein and cleaved H-kininogen were significantly lower in women with preeclampsia compared to the controls, p≤0.005, whereas the concentration of coagulation factor XII, H-kininogen and complement C1 esterase inhibitor was not significantly different, p>0.05. Conclusion This study demonstrates significant reduction in PKa generating capacity, PK and cHK indicating that the contact system is affected in PE suggesting a link to the pathophysiology of the disease.